THE INFLUENCE OF LEVERAGE, EXECUTIVE INCENTIVES, MANAGERIAL OWNERSHIP ON TAX AGGRESSIVENESS (STUDY IN MANUFACTURING COMPANIES LISTED ON IDX YEAR 2012-2014) - Shiddiq Multazam; Rahamwaty Rahamwaty (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This study aims to examine the influence of leverage, executive incentive and managerial ownership on tax aggressiveness. For measuring tax aggressiveness, this study uses Effective Tax Rates (ETR) as a proxy of tax aggressiveness.The samples of this study are the manufacturing companies listed on IDX (Indonesia Stock Exchange) in 2012-2014. The Samples are collected using purposive sampling method and resulted 60 companies as the final samples. The data needed for this study are collected from the companies’ annual report. Then, the data analyzed by multiple regression analysis. The results of this study show that (1) The leverage, executive incentives, and managerial ownership simultaneously influence the tax aggressiveness, (2) The leverage does not have influence on the tax aggressiveness, (3) The executive incentives does not have influence on the tax aggressiveness, (4) The managerial ownership have influence on the tax aggressiveness.